ANALYSIS THE IMPACT OF SILVIA APPLICATION IMPLEMENTATION ON THE EFFICIENCY AND EFFECTIVENESS OF PNBP CONTRIBUTIONS IN BPH MIGAS - Hidayat, Irvan Rizaldi; Katiya Nahda (Finance : International Journal of Management Finance, 2024)
This study aims to examine the impact of the SILVIA application implementation on the efficiency and effectiveness of Non-Tax State Revenue (PNBP) fee management within the Downstream Oil and Gas Regulatory Agency (BPH Migas). The research utilizes a qualitative approach through in-depth interviews and direct observations conducted during an internship program. The SILVIA application is designed to streamline PNBP management processes, encompassing payments, reconciliation, document creation (such as billing letters and minutes of meetings), and financial reporting.  The results indicate that the SILVIA application significantly enhances the efficiency and effectiveness of PNBP management. In terms of effectiveness, the program's success is demonstrated by several indicators, including achieving program objectives, user satisfaction, and increased output relative to input. Processes that were previously manual are now automated through the application, expediting the creation of essential documents and increasing the number of business entities successfully reconciled within a given period. Moreover, user satisfaction levels were positive, despite some technical challenges that still need to be addressed. In conclusion, the SILVIA application has a substantial impact on supporting the management of PNBP fees in BPH Migas. These findings are expected to broaden the understanding of the importance of digital innovation in improving the efficiency and effectiveness of government agency operations and provide input for the development of more optimal systems in the future.